2022
DOI: 10.3390/jcm11133582
|View full text |Cite
|
Sign up to set email alerts
|

Oral Valganciclovir Therapy in Infants Aged ≤2 Months with Congenital Cytomegalovirus Disease: A Multicenter, Single-Arm, Open-Label Clinical Trial in Japan

Abstract: Our aims were to determine the clinical impact of oral valganciclovir (VGCV) in infants aged ≤2 months with congenital cytomegalovirus (CMV) disease and evaluate the efficacy of VGCV when initiated beyond the neonatal period. The multicenter, single-arm, open-label clinical trial was conducted in Japan. Twenty-five infants aged ≤2 months with congenital CMV disease involving the central nervous system were enrolled and treated with VGCV for 6 months. The primary endpoint was the change in the whole blood CMV l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…The therapy was administered to 21 infants but was discontinued for 3 infants during the therapy because of neutropenia. The effectiveness of VGCV has also been reported [ 10 ]. CMV viral loads in whole blood, plasma, and urine samples from baseline to the end of therapy were analyzed in 21 patients (276 sample collection points).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The therapy was administered to 21 infants but was discontinued for 3 infants during the therapy because of neutropenia. The effectiveness of VGCV has also been reported [ 10 ]. CMV viral loads in whole blood, plasma, and urine samples from baseline to the end of therapy were analyzed in 21 patients (276 sample collection points).…”
Section: Resultsmentioning
confidence: 99%
“…However, VGCV therapy for symptomatic infants with cCMV is not the standard therapy in Japan. Therefore, the Japanese congenital cytomegalovirus study group conducted a multicenter, open-label, single-arm clinical trial [ 9 , 10 ]. To evaluate the viral load during VGCV treatment, the amount of CMV DNA in whole blood has been measured using quantitative PCR assays in previous studies.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of initiation of antiviral therapy before 1 month of age is based on studies in symptomatic infants ( 11 , 12 ), likely infected in early pregnancy, however it is important to reassess the evidence on timing of antiviral initiation as new data evolves. For example, a small recent Japanese study in symptomatic infants with high viral loads demonstrated no difference in SNHL outcomes up to 6 months follow-up between initiation of valganciclovir at <1 month, compared to 1–2 months of age ( 55 ). Data is limited on treatment of asymptomatic infants, likely to have been infected during late pregnancy, but in whom the risk of late-onset complications exists ( 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Antiviral therapy is not currently administered to infants who are diagnosed with symptomatic infection later in life. Two small retrospective observational series have reported improved hearing outcome in treating older infants ( 115 , 116 ), and a small multicenter, single-arm, open-label study observed no differences in hearing efficacy between the younger (14–28 days old) and older age (31–66 days old) groups ( 117 ). However, the preliminary data of a phase II, double-blind, randomized placebo-controlled trial of children from 1 month to 4 years of age (ClinicalTrials.gov Identifier: NCT01649869) on 35 children enrolled (median age of 18.7 months) showed no impact of treatment on hearing outcomes.…”
Section: Prevention and Treatment Of Congenital CMV Infectionmentioning
confidence: 99%